TEACHING READING NARRATIVE TEXT BY USING INDUCTIVE METHOD - Ani Nurani Sumantri (Journal of English Education Program (JEEP), 2014)
This study deals with teaching reading narrative text by using inductive method. This issue is discussed in accordance with the theories developed by Prince and Felder (2006) state that in inductive method, the teacher starts the lesson from specifics, teacher introduces topics by presenting specific observations or problems, encourage and guide students to discover them underlying principles for themselves. This study was conducted at the eleventh grade of one Senior High School in Ciamis that consist of 37 students. It employed a case study design. The data were obtained from several sources, including classroom observation and the students’ questionnaire. The data from classroom observation were analyzed by classified, coded, interpreted and commented the results of classroom observation from field notes and video recorder in each meeting. In analyzing the questionnaire the writer used display interpretation based on the percentage of the computation which displayed into 10 tables completed with the description and conclusions from each item. These findings revealed that teaching reading narrative text by using inductive method shows the positive results. Most of the students (70,27%) responded that students could learned read narrative text by used inductive method. Based on these findings, it is recommended that inductive method can be used as an alternative way to teach reading narrative text to Senior High School or Junior High School. The teacher at Senior High School should give the students opportunities to try to analyze the text and reading text before the beginning of lesson. In this regard, inductive method can be implemented in teaching reading narrative text to enhance students’ reading ability. Furthermore, this study also improved the students’ social skills such as team works, responsibility, critical thinking and solving problems together.